Resources, Agriculture, and Economic Growth in Economies in Transition - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper reviews some reasons why natural resource abundance and extensive agriculture appear to impede economic growth around the world. The paper presents empirical, cross-sectional evidence of various aspects of this relationship in the transition economies in Central and Eastern Europe and Central Asia since 1990. The essence of the argument is that heavy dependence on natural resources and agriculture may result in rent seeking (e.g., corruption) and policy failures (e.g., inflation) and may, moreover, discourage education, external trade, and genuine saving, thereby retarding economic growth. The paper concludes with a brief discussion of the policy implications of the analysis.
Keywords: 330